Cognitive–motor exergaming training in an older patient with depression and psychotic symptoms - Maja Tkaličanac (Physiotherapia Croatica, 2026)
Introduction: Depression in older adults is frequently associated with psychomotor slowing, impaired mobility, and increased fear of falling. The aim of this paper is to describe the effects of cognitive–motor exergaming training on functional mobility and fear of falling in an older patient with a severe depressive episode and psychotic symptoms. Case presentation: A 75-year-old female patient was hospitalised at the Department of Psychogeriatrics, University Psychiatric Hospital Vrapče, Zagreb, Croatia, due to a severe depressive episode with psychotic symptoms (F32.3). During hospitalisation, physiotherapy interventions were performed with emphasis on cognitive–motor exergaming training using the Dividat Senso platform between March 2025 and March 2026, with a four-month interruption due to significant psychiatric deterioration. Conclusion: During exergaming sessions, the patient demonstrated better functional performance, safer movement, and reduced fear of falling compared with everyday hospital activities. Functional mobility gradually improved despite persistent fear of falling. Cognitive–motor exergaming training may represent a useful physiotherapy intervention in psychogeriatric patients with complex psychomotor impairments.